Corporate Social Responsibility Influence on Customer Trust: The Mediating Effects of Reputation and Word of Mouth - Fatmawati, Indah; Fauzan, Nizar (Universitas Muhammadiyah Yogyakarta, 2020)
Research background, nowadays in the globalization era of each company is not only focused on getting profits, but the companies have CSR program as the primary concern of each company around the world. CSR is an excellent program for each company to invest long term relationships with the community, environment, and social. Research problem, this study aims to analyze corporate social responsibility on customer trust: the mediating effects of reputation and word of mouth in PT. Indofood Sukses Makmur.The literature review in this study focuses on the influence of corporate social responsibility on customer trust, and explore the mediating effects on reputation and word of mouth. Methodology, the respondents are consumers who have experience purchasing products and knows CSR programs in Indofood. This study applies structural equation modeling (SEM) to test the hypotheses. Results, the findings of this study, corporate social responsibility has a negative impact customer trust. CSR has significant positive impacts on corporate reputation and word of mouth. The mediating effect has positive relationship between reputation and word of mouth.